Las competencias investigativas en la educación superior - Hernández Navarro, Marlene Isabel (2019)
Research skills are necessary to carry out an optimal and efficient research process. Quality is understood to be the search for excellence in all areas. The purpose of this work was to systematizesome theoretical considerations regarding the quality of research skills in higher education.A bibliographic review of several theoretical references was carried out. A total of 25 sources of themwere consulted,76% of the last five years, available in databases such as: Latindex, SciELO, Scopus, Lilacs.Different updated conceptions are offered about the factors involvedtraining and developing research skills in higher education. It is concluded that competency training should be present in all higher education institutions.Continuous improvement in university processes is an imperative for the new university and a permanent goal to achieve excellence in higher education.